The impact of dyspepsia on symptom severity and quality of life in adults with headache. - Mei-Ling Sharon Tai; Norbelinda Norhatta; Khean Jin Goh; Foong Ming Moy; Ramanujam Sujarita; Azman Ahmad Asraff; Qin Zhi Lee; Jiun Hoong Ng; Eugene Choon Li Tan; Sanjiv Mahadeva (PLoS ONE)
Background Dyspepsia and headache frequently co-exist, but the clinical implication of this association is uncertain. We planned to examine the prevalence and impact of dyspepsia in adults with headache. Methods A cross-sectional study was conducted in a secondary care setting. Clinical, psychological and health-related quality of life (HRQOL) data were compared between subjects with headache and controls (non-headache subjects). The impact of dyspepsia was analysed further in subjects with headache alone. Results 280 subjects (93 cases with headache and 187 matched controls) were recruited. The following baseline characteristics of subjects were as follows: mean age 45.0 ± 17.3 years, 57.0% females and ethnic distribution-Malaysian = 45 (48.4%), Chinese n = 24 (25.8%) and Indians n = 24 (25.8%). Headache sub-types among cases with headache were as follows: tension-type headache (TTH) n = 53 (57.0%) and migraine n = 40 (43.0%). Dyspepsia was more prevalent in cases with headache compared to controls (25.8% vs 12.8%, p = 0.011), and headache was independently associated with dyspepsia (OR 2.75, 95% CI 1.39-5.43). Among cases with headache, there was a trend towards a higher prevalence of dyspepsia in those with migraine (27.5%) compared to TTH (24.5%). Subjects with headache and dyspepsia, compared to those with headache alone, had a greater severity of headache symptoms (63.67 ± 22.85 mm vs 51.20 ± 24.0 mm VAS, p = 0.029). Overall HRQOL scores were lower in headache subjects with dyspepsia (EQ-5D summary score 0.82 ± 0.18 vs 0.90 ± 0.16, p = 0.037 and EQ-5D VAS 62.08 ± 17.50 mm vs 72.62 ± 18.85 mm, p = 0.018), compared to those without dyspepsia. Conclusion Dyspepsia is associated with more severe headache symptoms and results in a lower HRQOL in patients with headache.